Comparative effects of graphene and graphene oxide on copper toxicity to Daphnia magna: Role of surface oxygenic functional groups. (May 2018) - Liu, Yingying; Fan, Wenhong; Xu, Zhizhen; Peng, Weihua; Luo, Shenglian
Abstract: Although the risk of graphene materials to aquatic organisms has drawn wide attention, the combined effects of graphene materials with other contaminants such as toxic metals, which may bring about more serious effects than graphene materials alone, have seldom been explored. Herein, the effects of graphene (GN) and graphene oxide (GO, an important oxidized derivative of graphene) on copper (Cu) toxicity to Daphnia magna were systematically investigated. The results indicated that GN remarkably increased the Cu accumulation in D. magna and enhanced the oxidative stress injury caused by Cu, whereas did not significantly alter D. magna acute mortality within the tested Cu concentrations (0–200 μg L −1 ). On the contrary, GO significantly decreased the Cu accumulation in D. magna and alleviated the oxidative stress injury caused by Cu. Meanwhile, the presence of GO significantly reduced the mortality of D. magna when Cu concentration exceeded 50 μg L −1 . The different effects of GN and GO on Cu toxicity were possibly dependent on the action of surface oxygenic functional group. Because of the introduction of surface oxygenic functional groups, the adsorption ability to metal ions, stability in water and interaction mode with organisms of GO are quite different from that of GN, causing different effects on Cu toxicity. This study provides important information on the bioavailability and toxicity of heavy metals as affected by graphene materials in natural water. Graphical abstract: Image 1 Highlights: The effects of GN and GO on Cu toxicity to aquatic organisms were compared. GN increased the accumulation of Cu in D. magna and enhanced the toxicity of Cu. GO decreased the accumulation of Cu in D. magna and alleviated the toxicity of Cu. Differences in the effects of GN and GO on Cu toxicity were caused by the surface oxygenic functional groups. Abstract : Differences in the effects of GN and GO on Cu toxicity were caused by the surface oxygenic functional groups.